2016
DOI: 10.1186/s12889-016-2812-8
|View full text |Cite
|
Sign up to set email alerts
|

Message on a bottle: are alcohol warning labels about cancer appropriate?

Abstract: BackgroundAlthough most Australians are unaware of the risk, there is strong evidence for a direct link between alcohol consumption and many types of cancer. Warning labels on alcohol products have been proposed as a cost-effective strategy to inform the community of this health risk. We aimed to identify how Australians might respond to such an approach.MethodsWe conducted a national online survey canvassing responses to four separate cancer warning messages on labels. The graphically presented messages were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
5
40
0
1
Order By: Relevance
“…The questionnaire was pilot-tested with a sample of 20 students in order to verify the comprehensibility of questions and the suitability of the language for the target in question. The final questionnaire comprised 30 questions, sub-divided into four sections:The first section analysed general habits and motivation of alcohol consumption, asking questions previously used in national and European surveys on alcohol consumption behaviour [3,18];The second section analysed awareness of health and social risks related to alcohol consumption by using seven statements from previous literature [14,15,16,32], asking consumers to express their agreement on a five-point scale (ranging from 1 = strongly disagree, to 5 = strongly agree). The internal reliability of these items was assessed through Cronbach’s alpha (α = 0.82).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire was pilot-tested with a sample of 20 students in order to verify the comprehensibility of questions and the suitability of the language for the target in question. The final questionnaire comprised 30 questions, sub-divided into four sections:The first section analysed general habits and motivation of alcohol consumption, asking questions previously used in national and European surveys on alcohol consumption behaviour [3,18];The second section analysed awareness of health and social risks related to alcohol consumption by using seven statements from previous literature [14,15,16,32], asking consumers to express their agreement on a five-point scale (ranging from 1 = strongly disagree, to 5 = strongly agree). The internal reliability of these items was assessed through Cronbach’s alpha (α = 0.82).…”
Section: Methodsmentioning
confidence: 99%
“…The internal reliability of these items was assessed through Cronbach’s alpha (α = 0.82). Furthermore, knowledge of alcohol content of different beverages and legal limits to drink and drive was tested by using two additional multiple-choice questions;The third section aimed to analyse attitudes towards information and health warnings on alcoholic beverages, using questions and statements from previous research (e.g., [30,32]). General attention and visibility of information on labels were tested with reference to specific information that may be currently (voluntarily) reported on alcoholic beverage labels: number of drinks not to exceed; drinking responsibly; and a warning related to drinking and driving (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been research examining the impact of alcohol warning labels on drinking intentions and behaviour, 18 and on the awareness of warning labels, 19 little is known regarding the impact of warning labels on increasing the knowledge of consequences of alcohol use. Recently, an online survey of 1,600 Australian adults demonstrated that the use of cancer warning statements on alcohol products could potentially increase the awareness of the link between alcohol use and cancer 20 …”
mentioning
confidence: 99%
“…Recently, an online survey of 1,600 Australian adults demonstrated that the use of cancer warning statements on alcohol products could potentially increase the awareness of the link between alcohol use and cancer. 20 The current study aimed to extend the limited literature on consumer knowledge of alcohol as a risk factor for adverse social and health outcomes by investigating awareness of a number of short-and long-term consequences of alcohol use among Australian adult drinkers. It also explored demographic correlates, including recognition of alcohol warning labels, of awareness of the consequences of alcohol use.…”
mentioning
confidence: 99%